Tuning dry reforming of methane for F-T syntheses: A thermodynamic approach. (1st October 2018) - Cao, Pengfei; Adegbite, Stephen; Zhao, Haitao; Lester, Edward; Wu, Tao
Highlights: Influences of temperature, pressure and CH4 /CO ratio on DRM were studied. Strategies to eliminate carbon formation during DRM were proposed. Relationship between operating parameters and H2 /CO ratio in syngas was revealed. DRM is tuned to yield syngas with a desired H2 /CO ratio for different F-T processes. Abstract: In this research, a thermodynamic equilibrium model was established using FactSage to study the way to tune H2 /CO ratio of syngas produced via dry (CO2 ) reforming of methane (DRM) for various F-T syntheses aiming at eliminating the use of a water–gas-shift unit. The effects of operating conditions, such as temperature, pressure and CH4 /CO2 mole ratio, on CH4 and CO2 conversion, H2 and CO yield, and solid carbon yield in DRM were investigated. These operating conditions were studied in a wide range, i.e., 550–1200 °C for temperature, 0.05–5 MPa for pressure and 0.5–2 for CH4 /CO2 mole ratio. The results showed that lower CH4 /CO2 ratios favoured high CH4 conversion and CO selectivity, but hampered CO2 conversion and H2 selectivity. However, the increase in pressure hindered CH4 conversion, CO2 conversion, H2 selectivity and CO selectivity except for carbon yield. Since the deactivation of catalyst associated with coke formation is the major obstacle for the industrialization of DRM process, a carbon-free regime of DRM was identified as CH4 /CO2 mole ratio = 1 and pressure = 0.1 MPa and temperature >1000 °C. Although the H2 /CO ratio could be adjusted by adjusting CH4 /CO2 mole ratio and/or pressure to satisfy the requirements of different F-T processes, the adjustment of CH4 /CO2 mole ratio was found to be a more efficient way of tuning H2 /CO mole ratio than adjusting operating pressure. The dependence of H2 /CO ratio in syngas on operating conditions of the DRM process was also revealed in this research. With the assistance of this relationship, optimal operating conditions for DRM could be quickly determined based on the required H2 /CO mole ratio for various typical F-T processes. It is shown that when the operating temperature of DRM was raised to over 700 °C, the H2 /CO ratio obtained at CH4 /CO2  ≤ 1 and P = 0.1 MPa was preferable for the synthesis of olefins, heavy hydrocarbons and oxygenated compounds. Otherwise the syngas was more suitable for the production of alkanes (C1 –C5 ).